2006
DOI: 10.1007/s11255-006-9015-7
|View full text |Cite
|
Sign up to set email alerts
|

Ten years outcome analysis of corporeal plication for Peyronie’s Disease

Abstract: Corporeal plication is an effective surgical option for the correction of penile deformity in patients with Peyronie's disease, with good cosmetic results and acceptable functional success rate in the long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Many studies reported similar results of plication compared with classical Nesbit's procedure and found plication to be equally effective (Mufti et al ., ) in treating the curvature and referring to postoperative patient's satisfaction (Geerstsen et al ., ; Thiounn et al ., ; Gholami & Lue, ; Adeniyi et al ., ; Fazili et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Many studies reported similar results of plication compared with classical Nesbit's procedure and found plication to be equally effective (Mufti et al ., ) in treating the curvature and referring to postoperative patient's satisfaction (Geerstsen et al ., ; Thiounn et al ., ; Gholami & Lue, ; Adeniyi et al ., ; Fazili et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Preoperative discussion of expected outcomes with surgery is important to assess the patient's goals of surgery and establish appropriate expectations . Several long‐term follow‐up studies have indicated moderate‐to‐high levels of dissatisfaction among patients receiving surgery . One study of PD patients undergoing surgical management, with >5 years follow up, reported dissatisfaction in approximately two‐thirds of patients, with recurrence of penile curvature, penile length loss and new‐onset ED being contributing factors .…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…One study of PD patients undergoing surgical management, with >5 years follow up, reported dissatisfaction in approximately two‐thirds of patients, with recurrence of penile curvature, penile length loss and new‐onset ED being contributing factors . Similarly, in a second long‐term study reviewing outcomes of corporeal plication surgery, 29% of patients reported dissatisfaction with function, primarily because of pain, ED and/or persistent deformity . Other long‐term studies with a minimum 4‐year follow up have reported dissatisfaction rates as high as 66%, with decreased penile length as a common complaint .…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…Potential complications associated with surgery include penile shortening, sensation change, recurrence of penile curvature, and subsequent erectile dysfunction (Chung et al, 2010;Kadioglu et al, 2006). Surgical complications or unexpected outcomes can have psychological consequences in addition to the psychological components of Peyronie's disease itself and may result in patient dissatisfaction with surgery (Akin-Olugbade et al, 2006;Chung et al, 2010;Fazili et al, 2007;Paez et al, 2007). Given the potential complications or recurrence of disease after surgery, patient expectations must be managed carefully (Akin-Olugbade et al, 2006;Hauck, 2006;Kim et al, 2008;Usta et al, 2003).…”
Section: Effects Of Treatment For Peyronie's Diseasementioning
confidence: 99%